Evaluation of Training with Elastic Bands on Strength and Fatigue Indicators in Paralympic Powerlifting - Felipe J. Aidar; Filipe Manuel Clemente; Luiz Fernandes de Lima; Dihogo Gama de Matos; Alexandre Reis Pires Ferreira; Anderson Carlos Marçal; Osvaldo Costa Moreira; Alexandre Bulhões-Correia; Paulo Francisco de Almeida-Neto; Alfonso López Díaz-; Eduardo Borba Neves; Breno Guilherme Araújo Tinoco Cabral; et al. (MDPI AG, 2021)
Background: Variable resistance training has recently become a component of strength and conditioning programs. Objective: This randomized counterbalanced cross-over study aimed to investigate the use of elastic bands (EB) and the traditional method (TRAD) and force indicators in a training session. Methods: 12 Paralympic athletes (age: 28.60 ± 7.60 years) participated in this three-week study. In the first week, the participants were familiarized with EB and TRAD and were tested for maximal repetition (1-RM). The research occurred in weeks 2 and 3, which included the pre-post training, during which the following measures were extracted: maximum isometric force (MIF), the peak torque (PT), rate of force development (RFD), fatigue index (FI), and time to MIF (Time). The athletes performed two tests, EB and TRAD, separated by a one-week interval. Results: Significant differences were found between the pre- and post-test for 1RM (p = 0.018, η2p = 0.412), MIF (p = 0.011, η2p = 0.415), PT (p = 0.012, η2p = 0.413), and RFD (p = 0.0002, η2p = 0.761). With the use of EB, there was a difference in RFD between TRAD before and EB after (p = 0.016, η2p = 0.761). There were significant differences in the before and after for FI between TRAD and EB (p < 0.001) and for Time (p < 0.001), indicating that training with the use of elastic bands promotes overload, characterized by increased fatigue and decreased strength. Conclusions: Training with EB did not decrease 1RM, PT, MIF or RFD, however, there was an increase in fatigue and time to reach MIF when compared to the method with fixed resistance.